2019
DOI: 10.1038/s41598-019-46719-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent spatial aggregation tendency of rainfall extremes over India

Abstract: Significant increase in the frequency of occurrences of rainfall extremes has been reported over several parts of the world. These extreme events were defined at individual grids without considering their spatial extent. Here, using ground-based observations over India during boreal summer, we show that the average size of spatially collocated rainfall extremes has been significantly increasing since 1980. However, the frequency of occurrences of such collocated extreme events remains unchanged. Around 90% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
3
41
1
Order By: Relevance
“…The LEREs occur in the southwestern sector of LPSs (Nikumbh et al, 2019). We observe that the LPS‐Lg are accompanied by SCVs on their western flank (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEREs occur in the southwestern sector of LPSs (Nikumbh et al, 2019). We observe that the LPS‐Lg are accompanied by SCVs on their western flank (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the physical processes that lead to extreme rainfall events (EREs) is a challenging multiscale problem that has received wide attention in the literature. The literature on EREs includes aspects like flash floods (Bosart & Sanders, 1981; Maddox et al, 1978, 1979), convective systems (Doswell III et al, 1996; Schumacher & Johnson, 2005), the observed trends (Goswami et al, 2006; Karmakar et al, 2017; Nikumbh et al, 2019; Rajeevan et al, 2008), and their future projections (Emori & Brown, 2005; Muller et al, 2011; O'Gorman, 2015; Trenberth, 1999). A multitude of extreme precipitation events, however, remained unpredicted (Coumou & Rahmstorf, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We then categorized extreme rainfall events with daily rainfall intensity exceeding 150 mm day −1 and extending over a wide region covering our area of interest (i.e., at least 10 grid cells over the MCZ must simultaneously satisfy the threshold of 150 mm day −1 ; e.g., Roxy et al, 2017). This will also ensure the defining of extreme events considering their spatial extent, following Nikumbh et al (2019).…”
Section: Identification Procedures For Extreme Rainfall Events and Cmentioning
confidence: 99%
“…The aforementioned studies mostly focus on wet spells, but a comprehensive process-oriented study focusing on the potential precursors leading to daily rainfall extremes has not been specifically addressed so far, except for in a few studies (Roxy et al, 2017;Nikumbh et al, 2019). Nikumbh et al (2019), while studying the observed increasing trend in the frequency of occurrences of large (i.e., spatially widespread events) rainfall extremes, noted that monsoon low pressure systems with precursory planetary scale conditions (e.g., over middle latitudes) may play a vital role for its increased occurrence. In contrast, Roxy et al (2017) suggest that precursory Indian Ocean warming may lead to more rainfall extremes over Indian landmass, with strengthened monsoon low-level westerlies transporting more moisture from Arabian Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Environment controlling factors, such as land use and rain represent chronic anthropogenic and intermittent natural disturbances, respectively [3][4][5] . The constant release of land-use-specific stressors through basal flow of water exerts a chronic anthropogenic (press) disturbance in the sedimentary ecosystems of TrUCS 1 from different land use types.…”
Section: Introductionmentioning
confidence: 99%